2017
DOI: 10.1016/j.physletb.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of fluctuating proton shapes on flow in proton-lead collisions at the LHC

Abstract: Results for particle production in √ s = 5.02 TeV p+Pb collisions at the Large Hadron Collider within a combined classical Yang-Mills and relativistic viscous hydrodynamic calculation are presented. We emphasize the importance of sub-nucleon scale fluctuations in the proton projectile to describe the experimentally observed azimuthal harmonic coefficients vn, demonstrating their sensitivity to the proton shape. We stress that the proton shape and its fluctuations are not free parameters in our calculations. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 103 publications
3
128
1
Order By: Relevance
“…Framework. We employ the hybrid framework described in [37] and [47], consisting of the boost-invariant IP-Glasma initial state, which provides the spatial (x ⊥ ) distribution of (locally anisotropic) energy-momentum tensors as input for the hydrodynamic simulation Music, which in turn is coupled to the hadronic transport simulation UrQMD, which describes the low energy density regime.…”
Section: Arxiv:190806212v1 [Nucl-th] 17 Aug 2019mentioning
confidence: 99%
“…Framework. We employ the hybrid framework described in [37] and [47], consisting of the boost-invariant IP-Glasma initial state, which provides the spatial (x ⊥ ) distribution of (locally anisotropic) energy-momentum tensors as input for the hydrodynamic simulation Music, which in turn is coupled to the hadronic transport simulation UrQMD, which describes the low energy density regime.…”
Section: Arxiv:190806212v1 [Nucl-th] 17 Aug 2019mentioning
confidence: 99%
“…Apart from the existence of alternative explanations, the applicability of hydrodynamics becomes increasingly doubtful as the system size decreases and gradients increase. Some recent studies argue that hydrodynamics should be applicable in systems of sizes down to ∼ 0.15 fm [9], but off-equilibrium corrections to particle distribution functions for momenta p T 0.5 GeV can be significant [10], which limits at least the quantitative reliability of the framework.So far all calculations of multi-particle correlations in small collision systems have studied either only intrinsic momentum correlations or purely final state driven ef- …”
mentioning
confidence: 99%
“…Besides the fundamental information on the gluonic structure of light nuclei at small x that exclusive vector meson production can provide, it also has applications for the phenomenology of high energy nucleus-nucleus collisions. To interpret deuteron-gold and helium-gold measurements at RHIC, it is important to have precise knowledge of the small-x geometry of light ions, which is an input for model calculations involving hydrodynamic simulations of QGP evolution (see [11] for a review and [13,[58][59][60][61] for more recent developments).…”
Section: Discussionmentioning
confidence: 99%
“…To verify this interpretation and to disentangle it from other sources of correlations, a good understanding of the proton geometry (and nucleon geometry in the nucleus) is required. It was shown that the flow measurements in LHC proton-lead collisions are compatible with a hydrodynamically evolving Quark Gluon Plasma (QGP), initiated with a Color Glass Condensate (CGC) initial condition, only if proton geometry fluctuations are included [12,13]. Similarly, the geometry fluctuations in the nucleons were found to be important in a global analysis of lead-lead and proton-lead flow data [14].…”
Section: Introductionmentioning
confidence: 99%